1994
DOI: 10.1111/j.1540-6288.1994.tb00399.x
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Heteroskedasticity and Global Stock Return Distributions

Abstract: This paper investigates conditional return distribution characteristics for seven developed markets (DMs) and eight emerging markets (EMs). With the exception of Germany and Japan, the behavior of monthly returns of DM sample countries is similar to that of the U.S. In contrast, EM returns exhibit a substantially greater degree of serial correlation and a higher incidence of autoregressive conditional heteroskedasticity (ARCH) in monthly data. Aggregation of returns into two‐ and three‐month holding periods de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…~ Even though institutional investors may trade less frequently than individual investors, their trades may more often be based on information. Although some have suggested that institutional investors are noise traders who engage in herd behavior [Errunza et al, 1994;Trueman, 1988], other evidence suggests that institutional investors are informed traders. Institutional investors devote substantial resources to information search [Potter, 1992].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…~ Even though institutional investors may trade less frequently than individual investors, their trades may more often be based on information. Although some have suggested that institutional investors are noise traders who engage in herd behavior [Errunza et al, 1994;Trueman, 1988], other evidence suggests that institutional investors are informed traders. Institutional investors devote substantial resources to information search [Potter, 1992].…”
Section: Discussionmentioning
confidence: 98%
“…Sample markets with significant ARCH are characterized by concentration of ownership, no forward or futures trading, higher transactions costs, and large bid-ask spreads. Errunza et al [1994] point out that these market features may affect the flow of information resulting in ARCH effects.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Sewell, et al, (1993) recorded evidence of linear dependencies in the stock markets of Japan, Korea, and Hong Kong. Yet, Errunza, et al, (1994) noted nonlinear dependencies in the stock markets of Japan, Germany, Brazil, Chile, Mexico, and India. Although, evidence on non-linearity has been recorded in literature, it has been inconclusive.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the empirical evidence indicated that: 1) Stock return distribution is not normally distributed but it is found to be leptokurtic (Fama E. , 1965), (Westerfield, 1977), (Hagerman R., 1978), (Peiró, 1999), (Valkanov, 2006), (Ghysels, 2007) among others. 2) Linear as well as non-linear dependency exists in stock prices (French & Roll, 1986), (Errunza, Hogan, Kini, & Padmanabh, 1994), (Booth & al, 1994), (Corhay & Rad, Daily returns from European stock markets., 1994), (Yadav, Paudyal, & Pope, 1999), among others; 3) Anomalies/Seasonalities in return distribution such as the day of the week effect, January effect, the holiday effect, the size effect and others do exist (Keim & Stambaugh, 1984), (Rogalski, 1984), (Jaffe, Jeffery, & Westerfield, 1985, 1989, (Smirlock & Starks, 1986), Wong et al(1992), (Cheung, Ho, & Draper, 1994), (Alexakis & Xanthakis, 1995), (Martikainen & Puttonen, 1990), among others. The main literature of characteristics of stock return was studied by (Hsieh D. , 1988).…”
Section: Literature Review and Theoretical Justification Of The Studymentioning
confidence: 99%